Creation of DABCO‐Based Amphoteric Ionic Liquid Supported TiO2 Nanoparticles: Execution of Amplified Catalytic Properties on Microwave‐Assisted Synthesis of N‐Substituted Pyrroles. Issue 11 (19th March 2019) - Mondal, Priya; Chatterjee, Sauvik; Bhaumik, Asim; Maity, Suvendu; Ghosh, Prasanta; Mukhopadhyay, Chhanda
Abstract: This is the first report of DABCO based amphoteric ionic liquid supported TiO2 nanoparticles, a supported catalyst with an ionic liquid layer (SCILL). It is highly efficient, recyclable, quasi heterogeneous catalyst for microwave assisted solvent free synthesis. Highly polar DABCO based ionic liquid with high dielectric constant of titanium dioxide nanoparticles enables the system as efficient microwave irradiation absorber. Amplified catalytic properties of this new combined green catalytic system have been first time implemented for the chromatography‐free synthesis of highly functionalised pyrrole moieties under microwave assisted solvent‐free conditions. The generation of catalyst and ionic liquid capping over titanium dioxide nanoparticles were characterised via Scanning Electron Microscopy (SEM), High Resolution Transmission Electron Microscopy (HRTEM), Thermo Gravimetric Analysis (TGA), Dynamic Light Scattering (DLS), Powder X‐Ray Diffraction (PXRD), Energy Dispersive Analysis X‐ray (EDAX) and Fourier Transform Infrared Spectroscopy (FT‐IR spectra). This combined quasi heterogeneous twin catalytic system, containing both acidic and basic environment afford the desired products in excellent yields within short reaction time. Here, the catalytic effect featuring the synergetic effect of titanium dioxide nanoparticles and amphoteric DABCO based ionic liquid were magnificently tethered. Abstract : Here we have reported a new, efficient DABCO based amphoteric ionic liquid ([DABCO‐C2 COOH] + [Br] − ). Using this [DABCO‐C2 COOH] + [Br] −, successful generation of TiO2 NP occurred from titanium tetra isopropoxide and at the same time we were able to produce DABCO‐C2 COOH] + [Br] − immobilised TiO2 NP (TiO2 ‐[DABCO‐C2 COOH] + [Br] − ). Using this TiO2 ‐[DABCO‐C2 COOH] + [Br] − as a catalyst we able to synthesize N‐aryl polysubstituted pyrroles under microwave assisted solvent free condition with good to excellent yield and short reaction time.